2019
DOI: 10.1049/mnl.2019.0340
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecules encapsulated TiO2nano‐cubes usingTinospora cordifoliafor photodegradation of a textile dye

Abstract: In the present research work, novel nano-sized cubes of TiO 2 capped with the biomolecules of Tinospora cordifolia leaf extract have been successfully synthesised and characterised. UV-visible absorption spectrum shows the maximum absorption edge at a wavelength of 271 nm. Transmission electron microscope results reveal the development of nano-sized cubes with anatase phase confirmed from selected-area electron diffraction pattern. Further, X-ray diffraction study reconfirms the crystallinity and anatase phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The X‐ray diffraction (XRD) study of the synthesized nanoparticles was analyzed and the result of this study indicate that the synthesized nanoparticles have good crystalline character with diffraction angle at 25.42, 38.17, 48.02, 54.23, 62.12 due to the different diffraction plane at (101), (003), (200), (105), (211). The outcome of our XRD study is in close agreement with other reported results and it also matched with the standard Joint Committee on Powder Diffraction Standards database (# 21‐1272) 34,35 . The sharp diffraction peaks appear in the XRD spectra of the synthesized nanoparticles demonstrate the crystallinity and the size of the nanoparticles.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The X‐ray diffraction (XRD) study of the synthesized nanoparticles was analyzed and the result of this study indicate that the synthesized nanoparticles have good crystalline character with diffraction angle at 25.42, 38.17, 48.02, 54.23, 62.12 due to the different diffraction plane at (101), (003), (200), (105), (211). The outcome of our XRD study is in close agreement with other reported results and it also matched with the standard Joint Committee on Powder Diffraction Standards database (# 21‐1272) 34,35 . The sharp diffraction peaks appear in the XRD spectra of the synthesized nanoparticles demonstrate the crystallinity and the size of the nanoparticles.…”
Section: Resultssupporting
confidence: 91%
“…results. 31,32 The FTIR spectra of the Bioinspired inorganic metal oxide nanoparticles was shown in 34,35 The sharp diffraction peaks appear in the XRD spectra of the synthesized nanoparticles demonstrate the crystallinity and the size of the nanoparticles. The sharp diffraction peak also reveal the purity and anatase phase of the synthesized nanoparticles.…”
Section: Data Statistic Analysismentioning
confidence: 99%
“…Anatase NPs were obtained after filtering the solution and rinsing the precipitate with alcohol, calcining in a muffle furnace (400 °C, 3 h), and grinding in a crystal mortar pestle. This same method was previously used to obtain anatase nanocubes using Tinospora cordifolia leaf extract [ 104 ]. In this, it was observed that the control of the morphology provided by the extract’s biomolecules proved to be fundamental in the performance of the nanostructures for degradation of the neutral red (NR) dye: cubic TiO 2 was more efficient for dye photodegradation than non-cubic NPs, reaching a percentage of 93.4% against 65.3% after 120 min under UV illumination.…”
Section: Green Synthesis Methods Of Tio 2 and Zno Nanostructuresmentioning
confidence: 99%
“…The crystalline nature of the biosynthesized Ag NPs is confirmed by the clarity of the primary reflected peaks ( Al-Hakkani et al, 2022a , Al-Hakkani et al, 2022b ; Al-Hakkani et al, 2022c ). Additionally, smaller particle sizes tend to exhibit a higher degree of crystallinity ( Aisida et al, 2020 ; Amaliyah et al, 2020 ; Anchan et al, 2019 ; Harshiny et al, 2015 ; Hassan et al, 2023 ; Kaur et al, 2019 ; Onyedikachi et al, 2022 ; Vembu et al, 2022 ; Wang et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%